Risk Management in Nursing Services to Improve Patient Safety - Rossa, M. Adila; Siswosuharjo, Partono; Mardianti, Lina; Qohar, Abdul (LPPM AKPER FATMAWATI, 2024)
Patient safety is a key indicator of healthcare quality and is the responsibility of all healthcare workers, particularly nurses as caregivers who interact directly and continuously with patients. Adverse events such as medication errors, patient falls, and healthcare-associated infections remain common, demonstrating the need for effective risk management implementation in nursing services. This study aims to analyze the role of risk management in nursing services and its relationship to improving patient safety. The study employed a quantitative approach with a cross-sectional design. The subjects were nurses working in nursing service units, using a purposive sampling technique. Data were collected using a structured questionnaire that measured risk management implementation and patient safety levels. Data were analyzed using univariate, bivariate, and multivariate methods. The results showed that most nurses implemented moderate to high levels of risk management. Bivariate analysis demonstrated a significant relationship between risk management and patient safety. Furthermore, multivariate analysis demonstrated that risk management was the dominant factor influencing patient safety after controlling for other variables such as education and length of service. These findings confirm that systematic risk management implementation, supported by a strong safety culture and organizational commitment, can significantly improve patient safety. Therefore, the integration of risk management into nursing practice needs to be continuously strengthened through ongoing training, clear policies, and a non-punitive incident reporting system to continuously improve the quality of nursing care and patient safety